Self-Consolidating High-Strength Concrete Optimization by Mixture Design Method - (:unkn) unknown (AMER CONCRETE INST, 2010)
The demand for the combination of high-strength concrete (HSC) and self-consolidating concrete (SCC) placeability have been growing worldwide. Concrete mixture proportions for HSC and SCC have varied widely depending on many factors and sensitive interactions between components. In practice, many trial batches are often required to generate the data that enable identification of optimum mixture proportions. Statistical mixture design (SMD) methods based on experiments constitute a new application area and prove to be a useful tool in terms of providing cost-effective means of the concrete optimization. In this study, the self-consolidating HSC in the C100/115 concrete class was optimized using D-optimal design, which is the most popular because of its simple computation and because there were constraints on the eight mixture component proportions. Test results from 46 experimental runs were analyzed to reach an optimum mixture proportion. SMD methods provide a methodical scientific solution to what has, up until now, been a trial-and-error process.
Keywords: concrete mixture proportioning; high-strength concrete; self-consolidating concrete; statistical mixture design